(3CFeI GdgOis (3GdEeGe GdHNGQj(B.s - (3eLehYI NdjaI ddceHjhJQ(B.s ((3GdbGgQI (B:s (3eLehYI NdjaI ddceHjhJQ(B.s)
(3YOOGdMdbGJ (B-(3GdMdbI GdGhdi (B-(3GdJGfjI hGdKGdKI (B.s
(3SjfGQjh hMhGQ Cjef SdGeI(B- (3ENQGL MeOj GdfHhj (B.s
3cd (3eSdSd GFeI GdGSdGe (B.s
All age.
Keywords: (3GdJeKjd GdOQGejs -- (3JdjaRjhf(B.s